2011
DOI: 10.1016/j.canlet.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

N-nitroso compound exposure-associated transcriptomic profiles are indicative of an increased risk for colorectal cancer

Abstract: Endogenous formation of N-nitroso compounds (NOCs), which are known animal carcinogens, could contribute to human carcinogenesis but definitive evidence is still lacking. To investigate the relevance of NOCs in human colorectal cancer (CRC) development, we analyzed whole genome gene expression modifications in human colon biopsies in relation to fecal NOC exposure. We had a particular interest in patients suffering from intestinal inflammation as this may stimulate endogenous NOC formation, and consequently pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Recently, human studies have demonstrated that indeed under normal dietary conditions urinary markers of exposure to N-nitroso compounds are associated with micronucleus frequencies, a validated marker of carcinogenic risk, as well as with gene expression changes that are involved in cancer development (Hebels, Jennen, et al, 2011). Similar gene expression changes were also found in colonic biopsy material after a human intervention study with red meat (Hebels, Sveje, et al, 2011;Hebels et al, 2012).…”
Section: N-nitroso Compoundsmentioning
confidence: 79%
“…Recently, human studies have demonstrated that indeed under normal dietary conditions urinary markers of exposure to N-nitroso compounds are associated with micronucleus frequencies, a validated marker of carcinogenic risk, as well as with gene expression changes that are involved in cancer development (Hebels, Jennen, et al, 2011). Similar gene expression changes were also found in colonic biopsy material after a human intervention study with red meat (Hebels, Sveje, et al, 2011;Hebels et al, 2012).…”
Section: N-nitroso Compoundsmentioning
confidence: 79%
“…Members of the latter NOC category, however, were found to activate a rich set of transcripts of the cell cycle and apoptosis pathways in Caco-2 cells and in biopsies of human volunteers (Hebels et al, 2009;Hebels et al, 2011). An ensuing report of the same research group showed ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 24 that a diet rich in red meat, in patients suffering either from inflammatory or irritable bowel syndrome, correlates positively to activation of a range of pro-neoplastic genes, as revealed by gene expression analysis.…”
Section: Red Meat Consumption and Noc-mediated Cellular Insultmentioning
confidence: 99%
“…colorectal cancer. Colorectal cancer is the third most common type of cancer in humans (Hebels et al, 2011;Kim et al, 2013). Nevertheless, in meat several potential anticarcinogens can be found including omega-3 polyunsaturated fatty acids (especially in fish) or conjugated linoleic acid (present in ruminant meats, e.g.…”
Section: Meat In the Dietmentioning
confidence: 99%